The anaerobic corrosion of candidate disposal canister materials in compacted bentonite exposed to natural granitic porewater containing native microbial populations. Issue 1 (30th September 2020) - Reddy, Bharti; Padovani, Cristiano; Rance, Andrew P.; Smart, Nick R.; Cook, Angus; Haynes, Haydn M.; Milodowski, Antoni E.; Field, Lorraine P.; Kemp, Simon J.; Martin, Andrew; Diomidis, Nikitas
Abstract: The materials corrosion test (MaCoTe) is a long‐term, multinational in situ corrosion experiment setup at the Grimsel Test Site, Switzerland. The experiment has been operating since 2014 with a focus on the corrosion behaviour of container materials for the disposal of high‐level waste and spent nuclear fuel under conditions representing a granitic deep geological repository. The experiment consists of eight modules containing metal coupons and bentonite. Two of the modules, each with a different bentonite density, have been retrieved after 394 days of exposure and have been analysed using a range of techniques aimed at studying the corrosion behaviour of the metals and the mineralogical evolution of the bentonite. Weight loss measurements show that carbon steel had a relatively low average corrosion rate ( 2 µm year −1 ). Much lower average corrosion rates were measured for the various types of copper (0.13–0.32 µm year −1 ). No detectable corrosion was measured on stainless steel coupons. To date, no significant differences were observed in the corrosion behaviour and rate of the test metals in bentonite with different dry densities. Abstract : The in situ corrosion of waste container materials in a bentonite buffer exposed to granitic porewater was investigated at Grimsel, Switzerland. After 394 days of exposure, the corrosion of carbon steel and copper was low, with no corrosion of stainless steel detected. No significant differences in corrosion rates were observed between individual bentonite dry densities.